26 CARDIOMYOPATHY RESULTS IN DYSREGULATION OF ENDOCARDIAL THROMBOMODULIN AND AN ALTERED PROTEIN C ACTIVATION PATHWAY. (1st March 2006) - Kim, A. Y.; Russell, H. M.; Raman, J.; Gupta, M.; Tian, X.; Lang, R. M.; Miller, J. L.
Abstract : Cardiomyopathy (CM) is associated with a significant risk for thrombosis and an increased risk for thromboembolic events. Early studies invoked blood stasis or flow disturbance as the principal underlying mechanisms. More recent evidence has linked CM with a hypercoagulable state, as demonstrated by elevated levels of thrombin-antithrombin complexes, prothrombin fragment F1+2, and fibrinopeptide A, all indices of thrombin activation. Thrombomodulin (TM), an integral membrane protein found on the endocardial endothelium (EE), is a potent thrombin inhibitor via activation of the protein C pathway. We hypothesized that the increased ventricular wall tension characteristic of CM would result in reduced TM protein expression on the surface of EE, which would, in turn, result in an impairment of local activated protein C (APC) activity, thereby increasing the risk for thrombosis. Using a rabbit pacing-induced CM model, we quantified TM protein expression on EE over time by digital immunohistochemical analysis ( n = 4/time point), expressed as arbitrary units (AU)/mm of left ventricular (LV) perimeter. Baseline TM staining of LV endocardial segments was 1, 669 ± 128 AU/mm. After 8 weeks of rapid pacing, TM protein expression on EE was markedly decreased (175 ± 41 AU/mm, p < .0001 vs control LV). TM protein expression remained significantly low after 15 weeks of pacing compared to control LV (142 ± 32 AU/mm, p < .0001). Western blot analysis confirmed the immunohistochemical pattern of reduced TM protein expression in CM. Persistence of staining for von Willebrand factor, which is stored in intracellular Weibel-Palade bodies, provided evidence that decreased TM staining was not due to endocardial loss. To assess the physiologic consequence of reduced TM expression, we measured in situ formation of APC using a chromogenic assay. Segments of control LV (n = 4) generated 2, 100 ± 138 fmol APC/min/cm 2 . In contrast, LV harvested after 8 and 15 weeks of pacing generated only 329 ± 35 and 307 ± 78 fmol APC/min/cm 2, respectively ( p < .0001 vs control LV). Conclusion: Endocardial TM protein expression is reduced by 90% at 8 weeks and 92% at 15 weeks following rapid pacing. This decrease in TM results in an 85% reduced capacity of the EE to generate activated protein C compared to normal LV. Reduced TM expression in CM markedly impairs APC formation, thereby contributing to a significant loss of endocardial thromboresistance.